Mechanical evaluation of implanted calcium phosphate cement incorporated with PLGA microparticles - Link, Dennis P. (2006)
In this study, the mechanical properties of an implanted calcium phosphate (CaP) cement incorporated with 20wt% poly (DL-lactic-coglycolic acid) (PLGA) microparticles were investigated in a rat cranial defect. After 2, 4 and 8 weeks of implantation, implants were evaluated mechanically (push-out test) and morphologically (Scanning Electron Microscopy (SEM) and histology). The results of the push-out test showed that after 2 weeks the shear strength of the implants was 0.4470.44MPa (average7sd), which increased to 1.3471.05MPa at 4 weeks and finally resulted in 2.6072.78MPa at 8 weeks. SEM examination showed a fracture plane at the bone–cement interface at 2 weeks, while the 4- and 8-week specimens created a fracture plane into the CaP/PLGA composites, indicating an increased strength of the bone–cement interface. Histological evaluation revealed that the two weeks implantation period resulted in minimal bone ingrowth, while at 4 weeks of implantation the peripheral PLGA microparticles were degraded and replaced by deposition of newly formed bone. Finally, after 8 weeks of implantation the degradation of the PLGA microparticles was almost completed, which was observed by the bone ingrowth throughout the CaP/PLGA composites. On basis of our results, we conclude that the shear strength of the bone–cement interface increased over time due to bone ingrowth into the CaP/PLGA composites. Although the bone–cement contact could be optimized with an injectable CaP cement to enhance bone ingrowth, still the mechanical properties of the composites after 8 weeks of implantation are insufficient for load-bearing purpose.